The Effect of Financial Distress and Capital Intensity on Tax Avoidance - Lutfi Hamdani Lutfi Hamdani; Intan Pramesti Dewi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the effect of financial distress and capital intensity on tax avoidance in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. Tax avoidance is an important concern because although legal, this practice can reduce potential state revenue, especially in a situation of economic recovery after the COVID-19 pandemic. This research is motivated by the inconsistency of previous research results regarding the relationship between financial distress and capital intensity variables with tax avoidance. The method used is a quantitative approach with descriptive research type. Data were obtained through purposive sampling technique from 32 companies, and analyzed using multiple linear regression. The results showed that financial distress has a significant negative effect on tax avoidance, while capital intensity has no significant effect. These findings indicate that companies in financial distress tend to avoid additional risk through tax avoidance. This study contributes to the understanding of corporate behavior in tax management and the importance of financial stability in fiscal compliance.